Correction to: The HIV epidemic in Colombia: spatial and temporal trends analysis - Jhon Freddy Montana; Glenda Roberta Oliveira Naiff Ferreira; Carlos Leonardo Figueiredo Cunha; Ana Angélica Rêgo de Queiroz; Wellington Augusto Andrade Fernandes; Sandra Helena Isse Polaro; Lucia Hisako Takase Gonçalves; Danielle Costa Carrara Couto; Elucir Gir; Renata Karina Reis; Wiliam Sorensen; Eliã Pinheiro Botelho (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.